Analisis Harga Pokok Produksi dan Penerapan Metode Cost Plus Pricing dalam Penetapan Harga Jual Usaha Kuliner De’Nara Catering: Analysis of the Cost of Production and the Application of the Cost Plus Pricing Method in Determining the Selling Price of De'Nara Catering Culinary Business - Wina Aulia Putri; Iis Sugiarti; Khania Balqis Naziha; Shavera Nurhaliza; Firman Reza Fahrevi (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
The rapid growth of the catering business requires business owners to determine selling prices accurately in order to achieve optimal profits and remain competitive in the market. However, some catering businesses still set selling prices without considering all production costs in detail. This condition causes the calculation of the cost of production to be less accurate and may affect business profitability. This study aims to analyze the calculation of the cost of goods manufactured (COGM) and the application of the cost plus pricing method in determining the selling price at De’Nara Catering. This research employed a descriptive quantitative method with a case study approach. Data were collected through interviews, observations, and documentation of production costs, with De’Nara Catering serving as the research object. The results indicate that the cost calculation method applied by the company does not include all factory overhead costs, resulting in a cost of goods manufactured (COGM) that is lower than the actual production cost. After recalculating the cost of production using the full costing method, the cost of production was found to be Rp28,000 per portion, while the selling price determined through the cost plus pricing method with a 25% profit margin was Rp35,000 per portion. The application of the cost plus pricing method was found to assist the company in determining a more accurate selling price in accordance with its targeted profit.